Efficacy of a county-wide schools weight management intervention. (November 2022) - Sanders, GJ; Marwa, WL; Wade, B; Gately, P
Aims: This study aimed to evaluate the effectiveness of the Local Authority commissioned large-scale public health service that provided a 6-week school-based weight management intervention for children aged 4–19 years. Methods: A quantitative retrospective cohort study identified participants from 130 schools consisting of 8550 potential children aged 4−19 years across a mixture of Lower Super Output Area (LSOA) deprivation groups. Participants were invited to take part in a 5- to 12-week Healthy Lifestyles intervention with a focus on weight management delivered by OneLife Suffolk between 1 January 2017 and 1 January 2020. This resulted in a final sample of 5163 participants. The following information for each child was collected anonymously: (1) age, (2) gender, (3) preprogramme body mass index (BMI), (4) postprogramme BMI, (5) weight category and (6) LSOA category. Results: Following the 6-week school-based intervention, there was a significant decrease in mean ΔBMI SDS (standardised body mass index) of −0.07 (−14.89%) among participants. Wilcoxon signed-rank test showed a significant change in weight status post 6-week weight management programme (WMP): BMI ( Z = −15.87, p < .001), BMI SDS ( Z = −21.54, p < .001), centile ( Z = −20.12, p < .01) and weight category ( Z = −7.89, p < .001), whereas Mann−Whitney U test showed no statistically significant difference in mean BMI SDS change between gender groups ( p = .24) and Kruskal−Wallis test revealed no statistically significant differences in mean BMI SDS change between child LSOA groups (c 2 (4) = 1.67, p = .796), school LSOA groups (c 2 (4) = 4.72, p = .317), ethnic groups (c 2 (4) = 2.53, p = .640) and weight category at the start of the intervention (c 2 (3) = 6.20, p = .102). Conclusions: This study contributes to the growing body of evidence demonstrating the efficacy of multicomponent school-based weight management interventions and demonstrates that such interventions can be successfully implemented as part of a wider healthy lifestyles service, without widening health inequalities.